2005
DOI: 10.1002/ejic.200500569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Half‐Sandwich Ruthenium(II) Complexes Bearing Alkenyl‐ and Alkynylphosphane Ligands

Abstract: [L = CO, X = SbF 6 , R = CH 2 CH=CH 2 (3a), CH 2 CH 2 CH=CH 2 (3b); L = PPh 3 , X = PF 6 , R = CH 2 CH 2 CH=CH 2 (4b)] have been prepared by treatment of the complexes 1a,b and 2b with a halide abstractor such as AgSbF 6 or NaPF 6 , respectively. Deprotonation reactions of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 54 publications
4
4
0
Order By: Relevance
“…Analytical and spectroscopic data (IR and 1 H, 13 C{ 1 H}, and 31 P{ 1 H} NMR) support the proposed formulation (see Experimental Section for details). The 31 P{ 1 H} NMR spectrum shows a singlet resonance at δ = −53.3 ppm, in accordance with the values obtained for analogous κ 3 ( P,C,C )-allylphosphane complexes [Ru(η 5 -C 5 H 5 ){κ 3 ( P,C,C )-Ph 2 PCH 2 CHCH 2 }(PPh 3 )][PF 6 ] (δ = −69.8 ppm) 1b. Although the two olefin faces are diastereotopic, the coordination to the metal center is completely selective since the 31 P{ 1 H} and 1 H NMR spectra of complex 1 indicate the presence of a sole stereoisomer.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Analytical and spectroscopic data (IR and 1 H, 13 C{ 1 H}, and 31 P{ 1 H} NMR) support the proposed formulation (see Experimental Section for details). The 31 P{ 1 H} NMR spectrum shows a singlet resonance at δ = −53.3 ppm, in accordance with the values obtained for analogous κ 3 ( P,C,C )-allylphosphane complexes [Ru(η 5 -C 5 H 5 ){κ 3 ( P,C,C )-Ph 2 PCH 2 CHCH 2 }(PPh 3 )][PF 6 ] (δ = −69.8 ppm) 1b. Although the two olefin faces are diastereotopic, the coordination to the metal center is completely selective since the 31 P{ 1 H} and 1 H NMR spectra of complex 1 indicate the presence of a sole stereoisomer.…”
Section: Resultssupporting
confidence: 86%
“…We have previously reported that ruthenium(II) complexes [Ru(η 5 -C n H m )(PPh 3 ){κ 3 ( P,C,C )-Ph 2 PCH 2 CHCH 2 }][PF 6 ] (C n H m = C 9 H 7 , C 5 H 5 ) react with alkynes and propargylic alcohols to give ruthenaphosphabicycloheptene complexes under mild thermal conditions (Chart ). These reactions take place through the formation of vinylidene or allenylidene derivatives, which undergo an unusual diastereoselective [2+2] intramolecular cycloaddition with allyl CC double bonds to generate the cyclobutylidene ring .…”
Section: Introductionmentioning
confidence: 99%
“…Analogous cases of parallel first‐ and second‐order kinetics were found in the study of the reactions of ruthenium complexes coordinated by the hybrid allylphosphane ligand, Ph 2 PCH 2 CH=CH 2 , which acts in a bidentate fashion through the coordination of both the phosphorus atom and the allylic double bond to the metal center. Mixed alkenyl‐phosphane or alkynyl‐phosphane ligands have attracted a large interest because of the potential hemilabile character in the corresponding transition metal complexes 28. The Cp* ruthenium complex [Ru(η 5 ‐C 5 Me 5 ){κ 1 ‐ P ‐Ph 2 PCH 2 CH=CH 2 }{κ 3 ‐ P , C , C ‐Ph 2 PCH 2 CH=CH 2 }][PF 6 ] ( 7 ), containing two molecules of allylphosphane in different, monodentate and bidentate, coordinative modes, reacts with nucleophiles (L = NaNCS, CO, PhC≡CH) yielding corresponding neutral or cationic complexes in which both molecules are monodentate.…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…These were found to be k 1 = 9(±2.5) × 10 –5 s –1 for phenylacetylene and 7(±1.5) × 10 –5 s –1 for p ‐chlorophenylacetylene, corresponding to the rate of formation of the vinylidene species [Ru(η 5 ‐C 9 H 7 )(=C=CHC 6 H 4 ‐ p ‐X){κ 1 ‐( P )‐PPh 2 (CH 2 CH=CH 2 )}(PPh 3 )] + , existing in equilibrium with the chelate complex. It is worth mentioning that a chelate complex analogous to 8 coordinated by the homoallylphosphane ligand PPh 2 (CH 2 CH 2 CH=CH 2 ) is inert toward reactions with either nitrile or alkynes 28. This information indicates that enlarging the chelate by one additional methylene group in the carbon chain imparts greater stability to the ring and to the ruthenium–olefin bond, which does not undergo either spontaneous or induced ring opening.…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…The dimeric chloro-bridged arene ruthenium [{(g 6 -arene)Ru(lCl)Cl} 2 ] (arene = benzene and their derivatives) and structurally analogous rhodium and iridium complexes [{(g 5 -C 5 Me 5 )M(lCl)Cl} 2 ] (M = Rh or Ir) imparting g 6 -/g 5 -cyclic hydrocarbon ligands are versatile and valuable synthetic intermediates that have seen many applications in coordination, organometallic chemistry and catalysis [1][2][3][4][5][6]. These complexes undergo a rich variety of chemistry via intermediacy of the chloro-bridge cleavage reactions leading to the formation of a series of interesting neutral and cationic mononuclear half-sandwich complexes [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%